Community Service for Strengthening Sumberingin Tourism Education with Rhythmic Waterwheels - Satworo Adiwidodo; Pondi Udianto; Bagus Wahyudi; Wirawan Wirawan; Eko Yudiyanto; Siti Duratun Nasiqiati Rosady; Kris Witono; Asrori Asrori (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
The Sumberingin Baths, a prominent landmark of Wringinsongo Village, represent one of the region’s most promising tourism destinations, supported by facilities such as photo spots, food stalls, places of worship, and gazebos for visitor comfort. Since 2022, the site has been enriched through the installation of an Archimedes Screw Turbine Micro Hydroelectric Power Plant (MHPP) as an educational display under the DIPA Swadana Partnership Community Service program. In 2023, the same initiative facilitated the construction of a café whose architectural design uniquely integrates natural and scientific elements, offering visitors a rare and engaging thematic experience. Despite these developments, the area remains limited in mechanical attractions that combine education with entertainment. Addressing this gap, the 2024 DIPA Swadana Regular Competition Community Service program introduced the installation of a rhythmic water wheel that harmonizes nature and technology. Designed as both a visual centerpiece and an interactive learning medium, the water wheel transforms water flow into rhythmic motion by driving musical instruments, thereby creating an innovative educational adventure that blends natural beauty with technological insight.